PROFIL SARANA DAN PRASARANA PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SMA NEGERI 1 TUMBANG SAMBA TAHUN 2021 - Effrata; Sontoe; Wisman, Yossita (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2021)
The purpose of this study was to describe the profile of physical education facilities and infrastructure at SMA Negeri 1 Tumbang Samba which can support the implementation of physical education learning. This research is descriptive research. The population in this study is the entire research subject, in this case the population to be studied in this study is the facilities and infrastructure for physical education, sports and health at SMA Negeri 1 Tumbang Samba. The results of the study show that the conditions of facilities and infrastructure for each sport are not the same, both for gymnastics, athletics, soccer, sepak takraw, volleyball, basketball, table tennis, martial arts and swimming. It was concluded that of the overall facilities and infrastructure for physical education, sports and health at SMA Negeri 1 Tumbang samba, the percentage yield was 61.2% with the ideal category.